Metformin Modulates High Glucose-Incubated Human Umbilical Vein Endothelial Cells Proliferation and Apoptosis Through AMPK/CREB/BDNF Pathway - Han, Xiqiong; Wang, Bilei; Sun, Yuning; Huang, Jia; Wang, Xin; Ma, Wenqi; Zhu, Yi; Xu, Rongfeng; Jin, Hong; Liu, Naifeng (Frontiers in Pharmacology, 2018)
Cardiovascular disease (CVD) is a leading cause of mortality and morbidity among patients with diabetes. Endothelial dysfunction is an early physiological event in CVD. Metformin, a common oral antihyperglycemic agent, has been demonstrated to directly affect endothelial cell function. Brain-derived neurotrophic factor (BDNF), originally discovered in the brain as a neurotrophin, has also been reported to play a protective role in the cardiovascular system. In our study, we demonstrated that high glucose (HG) reduced cell proliferation and induced cell apoptosis via changes in BDNF expression and that metformin reversed the effects of HG injury by upregulating BDNF expression. Furthermore, we found that cyclic AMP response element binding (CREB) phosphorylation was reduced in high glucose (HG)-treated human umbilical vein endothelial cells (HUVECs), and this effect was reversed by the metformin treatment. However, the metformin effect on BDNF levels in HG-incubated HUVECs was blocked by a CREB inhibitor, which indicated that BDNF expression is regulated by metformin through CREB activation. In addition, we found that adenosine monophosphate-activated protein kinase (AMPK) activation is involved in CREB/BDNF regulation in HG-incubated HUVECs treated with metformin and that an AMPK inhibitor impaired the protective effects of metformin on HG-treated HUVECs. In conclusion, this study demonstrated that metformin affects cell proliferation and apoptosis via the AMPK/CREB/BDNF pathway in HG-incubated HUVECs.